Using accelerometers in youth physical activity studies: a review of methods - Cain, Kelli L; Sallis, James F; Conway, Terry L; Van Dyck, Delfien; Calhoon, Lynn (Journal of physical activity & health, 2013)
In 2005, investigators convened by the National Cancer Institute recommended development of standardized protocols for accelerometer use and reporting decision rules in articles. A literature review was conducted to document accelerometer methods and decision rule reporting in youth physical activity articles from 2005-2010. Nine electronic databases identified 273 articles that measured physical activity and/or sedentary behavior using the most-used brand of accelerometer (ActiGraph). Six key methods were summarized by age group (preschool, children, and adolescents) and trends over time were examined. Studies using accelerometers more than doubled from 2005-2010. Methods included 2 ActiGraph models, 6 epoch lengths, 6 nonwear definitions, 13 valid day definitions, 8 minimum wearing day thresholds, 12 moderate-intensity physical activity cut points, and 11 sedentary cut points. Child studies showed the most variation in methods and a trend toward more variability in cut points over time. Decision rule reporting improved, but only 54% of papers reported on all methods. The increasing diversity of methods used to process and score accelerometer data for youth precludes comparison of results across studies. Decision rule reporting is inconsistent, and trends indicate declining standardization of methods. A methodological research agenda and consensus process are proposed.